Tooth loss and mobility in aggressive periodontitis patients: a retrospective study - Fazid, Nurul Farahin; So'odi, Siti Mahirah; Yaacob, Munirah; Husain, Juzaily; Muhammad Ali, Suhaila (2018)
Introduction and aims: Tooth loss has much negative implication in aesthetics and oral function of an individual. Aggressive periodontitis has been known to result in rapid tissue and bone destruction and if left untreated eventually tooth loss. Hence, this study was conducted to assess the prevalence of tooth loss and tooth mobility in a group of Aggressive periodontitis patients.